A Pyrosequencing-Based Assay for the Rapid Detection of the 22q11.2 Deletion in DNA from Buccal and Dried Blood Spot Samples - Koontz, Deborah (J Mol Diagn, 2014)
The 22q11.2 deletion syndrome is one of the most common deletion syndromes in newborns. Some affected newborns may be diagnosed shortly after birth because of the presence of heart defects, palatal defects, or severe immune deficiencies. However, diagnosis is often delayed in patients presenting with other associated conditions that would benefit from early recognition and treatment, such as speech delays, learning difficulties, and schizophrenia. Fluorescence in situ hybridization (FISH) is the gold standard for deletion detection, but it is costly and time consuming and requires a whole blood specimen. Our goal was to develop a suitable assay for population-based screening of easily collectible specimens, such as buccal swabs and dried blood spots (DBS). We designed a pyrosequencing assay and validated it using DNA from FISH–confirmed 22q11 deletion syndrome patients and normal controls. We tested DBS from nine patients and paired buccal cell and venous blood specimens from 20 patients. Results were 100% concordant with FISH assay results. DNA samples from normal controls (n = 180 cell lines, n = 15 DBS, and n = 88 buccal specimens) were negative for the deletion. Limiting dilution experiments demonstrated that accurate results could be obtained from as little as 1 ng of DNA. This method represents a reliable and low-cost alternative for detection of the common 22q11.2 microdeletions and can be adapted to high-throughput population screening.